HILAH SYAR’IYYAH MEMBAGI HARTA WARISAN SEBELUM MENINGGAL DUNIA: HILAH SYAR'IYYAH DIVISION OF INHERITANCE BEFORE THEIR DEATH - Ramadhana, Syahrin; Ihsan, Muhammad; Fathullah, Muhammad (Mitsaqan Ghalizan, 2022)
Inheritance is sometimes a problem that is not easy. Even though the division is actually very easy because the terms are clear. Many people then do the distribution of inheritance before death because they are worried that if the distribution of inheritance after death, the heirs will be in disagreement, and it is not uncommon to result in the breaking of friendship ties between them. Researchers want to analyze related to the theory of hiyal or hilah which is used in hilah syar'iyyah to divide inheritance before death. This study uses a qualitative method approach, with the primary source being books about hilah, while the secondary sources are books and books that help to analyze the problems in this research. In fact, the implementation of inheritance distribution is also related to the practice of hilah. In several areas in South Kalimantan, for example, it was found that some wealthy people distributed inheritance when they were still alive, known as living inheritance. There are several legal views regarding hilah in dividing inheritance before death